Activation of Nrf2 signaling: A key molecular mechanism of protection against cardiovascular diseases by natural products - Wu, Xiaoyu; Wei, Jiajia; Yi, Yang; Gong, Qihai; Gao, Jianmei (Frontiers in Pharmacology, 2022)
Cardiovascular diseases (CVD) are a group of cardiac and vascular disorders including myocardial ischemia, congenital heart disease, heart failure, hypertension, atherosclerosis, peripheral artery disease, rheumatic heart disease, and cardiomyopathies. Despite considerable progress in prophylaxis and treatment options, CVDs remain a leading cause of morbidity and mortality and impose an extremely high socioeconomic burden. Oxidative stress (OS) caused by disequilibrium in the generation of reactive oxygen species plays a crucial role in the pathophysiology of CVDs. Nuclear erythroid 2-related factor 2 (Nrf2), a transcription factor of endogenous antioxidant defense systems against OS, is considered an ideal therapeutic target for management of CVDs. Increasingly, natural products have emerged as a potential source of Nrf2 activators with cardioprotective properties and may therefore provide a novel therapeutic tool for CVD. Here, we present an updated comprehensive summary of naturally occurring products with cardioprotective properties that exert their effects by suppression of OS through activation of Nrf2 signaling, with the aim of providing useful insights for the development of therapeutic strategies exploiting natural products.